Gene Therapy Preserves Retinal Structure and Function in a Mouse Model of NMNAT1-Associated Retinal Degeneration - Greenwald, Scott H. (Mol Ther Methods Clin Dev, 2020)
No treatment is available for nicotinamide mononucleotide adenylyltransferase 1 (NMNAT1)-associated retinal degeneration, an inherited disease that leads to severe vision loss early in life. Although the causative gene, NMNAT1, plays an essential role in nuclear nicotinamide adenine dinucleotide (NAD)(+) metabolism in tissues throughout the body, NMNAT1-associated disease is isolated to the retina. Since this condition is recessive, supplementing the retina with a normal copy of NMNAT1 should protect vulnerable cells from disease progression. We tested this hypothesis in a mouse model that harbors the p.Val9Met mutation in Nmnat1 and consequently develops a retinal degenerative phenotype that recapitulates key features of the human disease. Gene augmentation therapy, delivered by subretinal injection of adeno-associated virus (AAV) carrying a normal human copy of NMNAT1, rescued retinal structure and function. Due to the early-onset profile of the phenotype, a rapidly activating self-complementary AAV was required to initiate transgene expression during the narrow therapeutic window. These data represent the first proof of concept for a therapy to treat patients with NMNAT1-associated disease.